Marketing Strategy Analysis in Increasing Sales Volume at Cafe Wong Paiton, Sapikerep Village, Probolinggo Regency - Kevin Ramadhany Sukmana; Yanda Bara Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the highly competitive cafe industry, effective marketing strategies are a key factor in achieving significant sales growth, the lack of understanding of these preferences is the background to the existence of research related to the analysis of marketing strategies in increasing sales at Cafe Wong Paiton Probolinggo, which is relevant and important to be carried out and uses the latest theories. The purpose of this study is to determine and analyze the marketing strategies used by Cafe Wong Paiton in increasing sales volume. This research is expected to be useful for the development of knowledge that has been learned by the researcher during his service in the Business Administration study program at the National Development University "Veteran" East Java. The study was conducted using a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats), which allows cafe management to formulate strategies that can increase competitiveness, efficiency, and business sustainability. By using this analysis, Cafe 41 can identify its strengths, such as product quality (coffee, food), customer service, or strategic location, which can be utilized to attract more customers and build a strong reputation in the market. The results of the study show that Cafe Wong Paiton is in Quadrant I with a value of (X; Y) of (1.97; 0.63), which indicates that this cafe is in a strategic position to implement an aggressive strategy. Cafe Wong Paiton in the Internal-External matrix is ​​​​in Quadrant I with a value of (X; Y) of (3.31; 3.25), which indicates that it is currently in a grow and build position. This position illustrates that Cafe Wong Paiton is in a growth stage, both in terms of sales, assets, and profits.